ANGKA REJECT DAN UPAYA MENGURANGI REJECT FILM PADA PEMERIKSAAN RADIOLOGI PERIAPIKAL GIGI - Sinta Sulastri; Ildsa Maulidya Mar'atush; Widya Mufida (Journal of Innovation Research and Knowledge, 2025)
Background: Periapical radiography is an intraoral imaging technique used to visualize the structures of the teeth and periapical tissues. During the Field Practice Program (PKL) at RS TK III dr. Soetarto Yogyakarta, it was found that the incidence of film rejects remained relatively high. Several contributing factors include unstable patient positioning, sudden movements during the procedure, and suboptimal communication of instructions during image acquisition. This condition is further exacerbated by the absence of fixation devices that could help maintain patient positioning, leaving radiographers to rely solely on verbal guidance. Therefore, research is needed to identify the factors contributing to the high rate of film rejects and to explore efforts that can be implemented to reduce them, thereby optimizing the quality of periapical radiographic images. Methods: This study used a descriptive qualitative approach with data collected through interviews with 5 patients and 3 radiographers, observation of examination procedures, and documentation of film reject data from July 1 to September 23, 2025. Data analysis was conducted through reduction, presentation, and conclusion drawing to obtain a comprehensive overview of the conditions in the Radiology Department of RS TK III dr. Soetarto Yogyakarta. Results: Film reject data showed consistently high rates: 31.4% in July, 28.2% in August, and 30% in September 2025. The dominant contributing factors were patient movement, improper cassette positioning, and miscommunication during radiographic procedures. Based on interviews, several patients reported difficulties in maintaining position and following the radiographer’s instructions, while radiographers stated that the absence of fixation aids posed an additional challenge in maintaining accurate positioning. Clearer communication efforts were found to help reduce positioning errors and patient movement. Conclusions:The high rate of film rejects in periapical radiography at RS TK III dr. Soetarto Yogyakarta is primarily caused by patient movement, cassette positioning errors, and suboptimal communication. Improving communication, providing pre-examination education, and supplying fixation tools have the potential to reduce film reject rates and improve the quality of periapical radiographic images